The political economy of the Arab uprisings - Cammett, Melani Claire, 1969- (Westview press spotlight, 2013)
"In this Westview Press Spotlight, Melani Cammett and Ishac Diwan explore the impact of the Arab Spring and subsequent events in the region. The Political Economy of the Arab Uprisings analyzes the ways in which salient socioeconomic and political factors are interacting to shape the construction of new political institutions and economic reform programs. The authors introduce students to events with vivid depictions of regional variations in the uprisings, pointing to a variety of factors that differentiate the countries of the region and help to explain their distinct trajectories thus far. The Political Economy of the Arab Uprisings is an extracted chapter from the 2013 Updated Edition of A Political Economy of the Middle East, Third Edition by Alan Richards, John Waterbury, Melani Cammett, and Ishac Diwan (ISBN 978-0-8133-4928-2). In the full-length edition, the authors present a comprehensive analysis of the transformation and development of the political economy in the Middle East over the past several decades. The book retains its focus on the interaction of economic development processes, state systems, and social actors as well as introduces coverage of the rising oil prices and how it reinforces authoritarian governance in the region, a refined assessment of "the Washington Consensus," the impact of the Arab Spring, and much more. "--